PENGARUH PROSES PEMERAMAN BUNGA CENGKEH TERHADAP MUTU CENGKEH KERING - Pote, Yulita Reda Bali; Tirtosastro, Samsuri; Tantalu, Lorine (Universitas Tribhuwana Tunggadewi, 2019)
Clove (Syzygium aromaticum) is one of the spice plant and cultivated in various regions in Indonesia. Dried clove flower mostly was used as a clove cigarettes ingredient. Another using for food flavor, pharmaceuticals and insecticides. More than 95% of the clove was planted by farmers, as a yard plant, and 5% as a interprise plantatationUntil now, drying of the fresh clove flower was worked direct after harvesting and used sunshine sun-drying. Result of dried clove show a large variation quality and lower quality. That result could to take place, because raw clove flower has a variation quality and sunshine also has a difference intencity during one day drying process. This study try to fermented raw or fresh clove before drying. Drying in this experiment used drier at 60oC. The goal of this research was to improve the dried clove by fermentation and stable temperature drying process. Randomized Completelly Design (RCD) was used for this experiment, with five treatment of fermentation, without fermentation, A1 = 24 hours fermentation, 48 hours fermentation, 72 hours fermentation, and 96 hours fermentation, respectivelly. After fermentation, clove flower was direct to dried by 60oC dryer. Experiment use three replication, and each treatment 150 gr of fresh flower clove. Result of the reseach showed 48-72 hours fermentation showed a high ratio dried to fresh clove (11,63-14,13%), and good colour (score = 6,20 â 6, 47), more brightness characteristic (score = 4,70â5,47) and more aromatic (7,33 â 7, 27). The last of three sensory parameter was test by panelis. The research results showed that curing treatment clove generate clove 48-72 hours dry with a higher yield than the way of drying out directly after the cloves is quoteddespite the colour, the brightness of the colours and aromas the same. Curing of 48-72 hours before the dryed was enough to produce a high yield with a dried cloves (11,63 â 14,13 %), as well as the colour (score = 6,20 â 6, 47), the brightness of the colors (score = 4,7 â 5,47), and aromas (7,33 â 7, 27). Cengkeh (Syzygium aromaticum) adalah tanaman rempah dan banyak ditanam di berbagai tempat di Indonesia. Bunga cengkeh kering banyak dipakai untuk bahan baku bumbu rokok kretek. Penggunaan yang lain adalah sebagai bahan pembawa rasa dan aroma makanan, farmasi dan insektisida. Lebih dari 95% tanaman cengkeh diusahakan petani, khususnya sebagai tanaman pekarangan dan 5% oleh perusahaan perkebunan. Sampai saat ini pengeringan bunga cengkeh dilakukan langsunng setelah panen dan menggunakan panas matahari. Hasil pengeringan umumnya mempunyai keragaman mutu yang tinggi dan cenderung bermutu rendah. Hal tersebut dapat terjadi karena cengkeh segar mempunyai variasi mutu yang tinggi dan intensitas panas matahari selama penjemuran juga tinggi. Penelitian ini melakukan fermentasi terhadap bunga cengkeh sebelum dikeringkan pada suhu pengering 60oC. Tujuan penelitian memperbaiki mutu cengkeh kering melalui fermentasi dan penggunaan suhu pengering yang stabil. Penelitian ini menggunakan Rancangan Acak Lengkap (RCD), dengan 5 (lima) perlakuan fermentasi. Perlakuan tersebut masing-masing A0=Tanpa fermentasi, A1=24 jam fermentasi, A2=48 jam fermentasi, A3=72 jam fermentasi dan 96 jam fermentasi. Setelah fermentasi bunga cengkeh langsung dikeringan didalam pengering dengan suhu 60oC. Percobaan diulang 3 (tiga) kali dengan 150 gr sampel bunga cengkeh segar. Hasil penelitian menunjukkan 48-72 jam fermentasi menghasilkan rendemen atau rasio berat kering terhadap berat basah paling tinggi (11,63-14,13%). Hasil uji panelis juga menunjukkan hasil paling baik, masing-masing warna (skor =6,20-6,47), kecerahn warna (skor=4,70-5,74), dan aroma (skor=7,33â7,27).